CHALLENGES IN TEACHING STUDENTS THE RUSSIAN LANGUAGE (Conferencea, 2023)
This article explores the challenges encountered in teaching the Russian language to students and provides strategies for effective instruction. The complexities of Russian grammar, the Cyrillic alphabet, pronunciation difficulties, limited exposure to authentic language, maintaining motivation, limited instructional resources, and diverse language backgrounds are identified as common problems in Russian language instruction. By employing targeted instructional approaches, incorporating engaging activities, providing exposure to authentic materials, and addressing individual needs, educators can overcome these challenges and create a supportive learning environment. The article emphasizes the importance of proactive problem-solving to facilitate successful language acquisition and foster students' appreciation for Russian culture and society.